Cerebral organoids: a promising model in cellular technologies - T. A. Shnaider (Вавиловский журнал генетики и селекции)
The development of the human brain is a complex multi-stage process including the formation of various types of neural cells and their interactions. Many fundamental mechanisms of neurogenesis have been established due to the studying of model animals. However, significant differences in the brain structure compared to other animals do not allow considering all aspects of the human brain formation, which could play the main role in the development of unique cognitive abilities for human. Four years ago, Lancaster’s group elaborated human pluripotent stem cell-derived three-dimensional cerebral organoid technology, which opened a unique opportunity for researchers to model early stages of human neurogenesis in vitro. Cerebral organoids closely remodel many endogenous brain regions with specific cell composition like ventricular zone with radial glia, choroid plexus, and cortical plate with upper and deeper-layer neurons. Moreover, human brain development includes interactions between different brain regions. Generation of hybrid three-dimensional cerebral organoids with different brain region identity allows remodeling some of them, including long-distance neuronal migration or formation of major axonal tracts. In this review, we consider the technology of obtaining human pluripotent stem cell-derived three-dimensional cerebral organoids with different modifications and with different brain region identity. In addition, we discuss successful implementation of this technology in fundamental and applied research like modeling of different neurodevelopmental disorders and drug screening. Finally, we regard existing problems and prospects for development of human pluripotent stem cell-derived threedimensional cerebral organoid technology.